1999
DOI: 10.1021/jf990326v
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Microbiological Characteristics of Ewes' Milk Cheese Manufactured with Extracts from Flowers of Cynara cardunculus and Cynara humilis as Coagulants

Abstract: The chemical and microbial characteristics as well as the flavor and aroma of Los Pedroches cheese made using aqueous extracts of Cynara cardunculus L. flowers were compared with those of cheeses manufactured with extracts of Cynara humilis L. throughout ripening. The two thistle species assayed were found to have no appreciable effect on the moisture, fat, protein, and NaCl contents of the cheese or on its water activity, flavor, and aroma; however, the use of C. humilis resulted in reduced lactic acid conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 23 publications
5
43
0
1
Order By: Relevance
“…However, the increasing consumption of cheese and the decreasing number of slaughtered calves have led to an increased price of calf rennet and a search for alternative milk coagulants. Those facts have been accompanied by the recent Bovine Spongiform Encephalomyelitis (BSE) disease in dairy cattle (Vioque et al, 2000). This situation encourages the search for other sources of rennet substitutes from microbial or plant sources to meet the needs of the expanding cheese industry.…”
Section: κ-Casein → ρ-κ-Casein (Insoluble)↓ + Macropeptide (Soluble) mentioning
confidence: 99%
“…However, the increasing consumption of cheese and the decreasing number of slaughtered calves have led to an increased price of calf rennet and a search for alternative milk coagulants. Those facts have been accompanied by the recent Bovine Spongiform Encephalomyelitis (BSE) disease in dairy cattle (Vioque et al, 2000). This situation encourages the search for other sources of rennet substitutes from microbial or plant sources to meet the needs of the expanding cheese industry.…”
Section: κ-Casein → ρ-κ-Casein (Insoluble)↓ + Macropeptide (Soluble) mentioning
confidence: 99%
“…In contrast, Fernández-Salguero and Sanjuán [24] showed that residual α s -and β-caseins were more concentrated in cheese produced with animal rennet than in cheese produced using plant coagulant (C. cardunculus), but no statistically significant differences were found between these two types of coagulant. Vioque et al [66] showed that WSN was higher in cheeses manufactured with extracts of C. cardunculus than with C. humilis, but WSN in cheeses with C. humilis was much higher than in Los Pedroches cheese manufactured with chymosin [24]. The electrophoretic patterns of the WISF of both cheeses were claimed to unfold a higher susceptibility of α s -than β-casein to proteolysis [24,36,53].…”
Section: Plant Coagulant Versus Animal Rennetmentioning
confidence: 99%
“…Cheeses manufactured with ovine milk using extracts from C. cardunculus as coagulant were compared with cheeses manufactured with commercial animal rennet [24,53], or with extracts of Cynara humilis [66]. Comparing averages and 95% confidence intervals, it has been stated [53] that the type of coagulant has no significant effect upon cheese bulk chemical composition throughout ripening, and that no significant microbiological differences were detected between cheeses manufactured with C. cardunculus or animal rennet.…”
Section: Plant Coagulant Versus Animal Rennetmentioning
confidence: 99%
See 2 more Smart Citations